Family controlled firm, governance mechanisms and corporate performance: Evidence from Indonesia - Eko Suyono (Universitas Hayam Wuruk Perbanas, 2016)
This study investigates, firstly, the influence of family-controlled firm on corporate performance, and secondly, the influences of corporate governance mechanisms including control variable on corporate performance in the companies listed on the Indonesian Stock Exchange. By using five years (2009-2013) company data, this study used Ordinary Least Square (OLS) regression to test the hypotheses. The results based on OLS, indicate that family controlled firms tend to have better performance than non Family controlled firms. Moreover, in regard to the link between governance variables and corporate performance, only managerial ownership exhibits a positive relation with corporate performance, for both proxies, i.e. Tobins Q and ROA. Yet, the rests of governance variables (i.e. institutional ownership, audit committee, board of directors and independent board of commissioners) do not confirm the relationship with corporate performance. These findings have significant policy implications for the government, regulatory bodies, companies and other stakeholders including the investors in Indonesia to shape and implement an optimal governance system that can improve corporate performance.